Numerical investigation of working fluid properties impacting performance of magnetocaloric cooling device. (5th January 2023) - Płuszka, Paweł; Malecha, Ziemowit; Lewandowski, Daniel; Surma, Kacper
Abstract: This paper presents a virtual experiment test stand of a magnetocaloric cooling device that utilizes the magnetocaloric effect (MCE). The virtual test stand is based on a comprehensive and novel numerical model that integrates pumps, check valves, tanks, and a gadolinium porous bed in a time-dependent system. The MCE is achieved by cyclic stages of magnetization and demagnetization of the porous bed of an active magnetic regenerator (AMR) and is synchronized with flow of a working fluid. The virtual test stand is utilized to investigate the influence of the properties of the working fluid on the performance of the cooling device. The isolated and combined effects of the density, specific heat, viscosity, and thermal conductivity of the working fluid are analyzed using the Design of Experiments (DOE) approach. The response variables considered are the temperature span between the cold and hot tanks and the available cooling load of the cold tank. The conducted study has revealed that the temperature span is majorly influenced by the isolated effects of thermal conductivity, specific heat, and density, whereas the cooling power is influenced by isolated and combined effects of most of the properties of the working fluid. The virtual test stand developed and the results achieved can be used to define an optimal working fluid and operational setting, such as the cycle frequency, mass flow, and bed structure of a real device. Highlights: Virtual test stand of a magnetocaloric cooling device was developed. The influence of thermophysical properties of the working fluid was investigated. DOE was used to study their isolated and coupled effects. Temperature span was mostly influenced by the isolated effects of thermal properties. Cooling performance was also influenced by the coupled effects.